Impact of Electronic Chronic Pain Questions on patient-reported outcomes and healthcare utilization, and attitudes toward eCPQ use among patients and physicians: prospective pragmatic study in a US general practice setting - Lamerato, Lois; Shah, Vinay; Abraham, Lucy; Cappelleri, Joseph C.; DeLor, Bonnie; Ellsworth, Stacy R.; Hegeman-Dingle, Rozelle; Park, Peter W. (Frontiers in Medicine, 2023)
Abstract Objective: The Electronic Chronic Pain Questions (eCPQ) has been developed to help healthcare providers systematically capture chronic pain data. This study evaluated the impact of using the eCPQ on patient reported outcomes (PROs) and healthcare resource utilization (HCRU) in a primary care setting, and patient and physician perceptions regarding use of, and satisfaction with, the eCPQ. Methods: This was a prospective pragmatic study conducted at the Internal Medicine clinic within the Henry Ford Health (HFH) Detroit campus between June 2017 and April 2020. Patients (aged ≥18 years) attending the clinic for chronic pain were allocated to an Intervention Group to complete the eCPQ in addition to regular care, or a control group to receive regular care only. The Patient Health Questionnaire-2 and a Patient Global Assessment were assessed at baseline, 6-months, and 12-months study visits. HCRU data were extracted from the HFH database. Telephone qualitative interviews were conducted with randomly selected patients and physicians who used the eCPQ. Results: 200 patients were enrolled, 79 in each treatment group completed all 3 study visits. No significant differences (P>0.05) were found in PROs and HCRU between the 2 groups. In qualitative interviews, physicians and patients reported the eCPQ as useful, and using the eCPQ improved patient-clinician interactions. Conclusions: Adding the eCPQ to regular care for patients with chronic pain did not significantly impact the PROs assessed in this study. However, qualitative interviews suggested that the eCPQ was a well-accepted and potentially useful tool from a patient and physician perspective. By using the eCPQ, patients were better prepared when they attended a primary care visit for their chronic pain and the quality of patient-physician communication was increased.